Intraoperative periprosthetic fractures during total hip arthroplasty in patients with rheumatic diseases - A. E. Khramov; M. A. Makarov; S. A. Makarov; V. N. Amirdzhanova; A. V. Rybnikov; V. P. Pavlov; A. A. Askerov (Научно-практическая ревматология, 2019)
Surgical treatment in patients with rheumatic diseases (RDs) is associated with the higher risk of complications due to the presence of the inflammatory process, to long-term therapy with glucocorticoids, disease-modifying antirheumatic drugs, and biologic agents (BA), to decreased physical activity, and the severity of functional disorders, and to obvious osteoporosis. All this increases the risk of intraoperative complications, including periprosthetic fractures.Objective: to comparatively analyze intraoperative periprosthetic fractures of the greater trochanter, acetabulum, and proximal femur during total hip arthroplasty (THA) in patients with RDs.Subjects and methods. From 1998 till 2017, a total of 1569 THA were performed in patients with RA, including 464 patients with rheumatoid arthritis (RA), 396 with juvenile rheumatoid arthritis (JRA) and systemic lupus erythematosus (SLE), and 709 with osteoarthritis (OA).Results and discussion. Periprosthetic fractures after THA were diagnosed in a total of 68 (4.33%) patients, including 23 (4.96%) patients with RA, 27 (6.82%) with JRA and SLE, and 18 (2.54%) with OA; 42 (61.8%) patients with periprosthetic fractures underwent osteosynthesis. Statistical analysis of the findings revealed significantly higher rates of complications in patients with RA and JRA with SLE (p < 0.005).Conclusion. The findings confirm that the risk of periprosthetic fractures is higher in patients with inflammatory diseases, including RA, JRA, and SLE. These patients require a special approach that involves medical correction of impaired bone metabolism and proper individual selection of endoprosthetic components, by taking into account the anatomical features of female patients and delicate bone handling during surgery.